Assessment of Females Awareness in Saudi Arabia about Long term use of COCP and Venous Thromboembolism Risk: A Cross Sectional Study - Basmah Mohammed Alazmi,; Shaikha Sulayyem Alsharari,; Razan motawkel,; Sara Alzahrani,; Anhar Alfateel,; Jinan Msallati,; Noora Abdulhafeedh Alsulami,; Abdulaziz Aloudah, (International Journal of Innovative Research in Medical Science, 2021)
Background: Nowadays there are a lot of women using contraceptive oral combined pills for birth control and as we know VTE is one of the complications when it used for a long time, and here in this study our aim is to assess the awareness and knowledge of females who live in Saudi Arabia about COCP and its complications like VTE. A cross-sectional observational study based on a questionnaire conducted among females who live in Saudi Arabia. Data collection was done by using online survey which contains questions about the age, education and contraception. Methods: An observational cross-sectional study carried out during December 2020 in Saudi Arabia. We minimize our target population through inclusion criteria: 1- Female 2- Live in Saudi Arabia 3- Agree to participate. Sample size was 454 participants calculated by using survey system website through sample size calculator with Confidence Level 95% and margin of error 5%. Result: A total of 454 patients completed the survey questionnaire. The results showed that the vast majority of the study participants aged 20 years or more. Moreover, more than 90% of the study participants were Saudi females. The average body weight is around 95 kg and height 164.2 cm. The results also indicated that two-third of the study participants attained university education level compared to 16.1% obtained secondary education. Additionally, 36.6% of the study participants worked as a housewife, 18.1% working in health field. Moreover, 40% of the respondents reside in the western regions, 34% live in eastern regions compared to the lowest percentage in South region 3.3%. Conclusion: In summary, this study revealed that the internet was the main source of knowledge. Health care providers should perform their intended role in improving the female’s awareness regarding family planning. The criteria for preferable contraceptive method are that it has few or no side effects, also it depends on how much effective and convenient it is. Educational programs may be warranted to minimize the fear of side effects and to enhance the general knowledge about contraception.